What quality factors matter in enhancing the perceived benefits of online health information sites? Application of the updated DeLone and McLean Information Systems Success Model. (May 2020) - Shim, Minsun; Jo, Heui Sug
Highlights: Information quality was the strongest predictor of perceived benefits of site use. User satisfaction and intention mediated the relationship between information quality and perceived benefits. Service quality led to perceived benefits via mediators. The role of system quality received no empirical support. Abstract: Background: Despite a growing need for designing and monitoring health information sites through comprehensive examination of the various elements of website quality, there is little research that systematically models and presents such examinations. Objectives: Applying the updated DeLone and McLean Model of Information Systems Success, this research aimed to examine how health information sites' information quality, system quality, and service quality lead to user satisfaction and perceived benefits. Methods: This research was conducted in a specific context of the National Health Information Portal (NHIP), a governmental health information site in South Korea. We conducted online survey in 2017, with 506 adults from the NHIP consumer panel. Data were analyzed using a confirmatory factor analysis, hierarchical ordinary least squares regression, and bootstrapping approach for a mediation test. Results: Of the three quality factors, information quality had significant associations with all outcome variables: user satisfaction, intention to reuse the site, and perceived benefits of site use in health settings. There were also indirect paths from information quality to perceived benefits, one mediated through intention and the other mediated through satisfaction and then intention. Service quality had a significant association with user satisfaction, and its impact on perceived benefits occurred indirectly through user satisfaction and intention in serial. By contrast, the role of system quality received no empirical support. Implications: The results offer theoretical and practical implications for how to enhance the effectiveness of online health information sites.